Warung Conversations - Kopi Luwak with Ni Luh Putu Sutarini (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
Interview with Balinese legong dancer Ni Luh Putu Sutarini born in the village of Peliatan in Gianyar regency in Bali. Putu has performed in several countries including Morocco, Japan and Singapore. She is considered one of the best legong dancers today. A disciple of the great dancer Sang Ayu Muklen from Pejeng village, Putu (45 years old), in addition to transmitting the dance tradition trough classes to young balinese and foreigners is also producer and administrative director of the Tri Pusaka Sakti Ensemble group – one of the most traditional and renowned in Bali, in Batuan Village.
Keywords: Legong; Drama-dance; Bali; Training